Rational organization and scientific management in the electronic environment of university libraries between reality and hope - damma, mostafa; barka, lahouari (Journal of Social Sciences and Humanities, 2023)
This study aims to highlight the status and importance of rational organization and scientific management in university libraries in the light of the electronic environment. Information in both paper and electronic forms and its availability, but it is a matter of skills, methods and self capabilities and investing in them efficiently and effectively, starting from selection and collection, acquisition, then organization and processing, then availability to the beneficiary. Finally, the study includes the role of rational organization and scientific management, the foundations and principles, and the roles assigned to the human element within the university library.